(untitled) (Nóema, 2023)
The article aims to investigate the transformations that educational institutions are undergoing under the pressure of European directives following neoliberal business-oriented models. Genealogical analysis and comparison with European and national institutional documentation suggest that the educational reforms of the last thirty years, focused on the logic of competencies and the business model, are designed to be a fundamental support for neoliberal subjectivation practices. The centrality of the notion of competence and the emphasis on the need to develop and apply an increasing number of knowledge measurement tools lead to the definition of an educational horizon whose main purpose is to train individuals useful to the productive system, both in terms of technical skills and values. An educational system with these objectives entails the distortion and devaluation of a whole range of knowledge areas, including philosophy. Competency-based teaching is transforming the study of philosophy from critical knowledge into a simple adaptation to evaluation systems that align with the logic of the business world: in the best-case scenario, a set of soft skills, and in the worst-case scenario, a true servant of corporate culture.